READINESS OF THE POSTGRADUATES ON THE UTILIZATION OF CLOUD COMPUTING FOR LEARNING IN UNIVERSITIES IN KWARA STATE, NIGERIA - Gboyega Ayodeji Aladesusi (Universitas Kuningan, 2021)
Cloud computing is one of the newer trends in technological innovations. It is a subscription- based service in which learners and the general users have access to vast number of services such as storage, space, processing and networking resources. However, despite the numerous benefits of cloud computing for learning, there is need for proper awareness and reorientation of Postgraduates towards the use of cloud computing for learning. This study investigated Postgraduates’ readiness to utilize cloud computing for learning in Universities in Kwara State, Nigeria. The objectives of the study were to: (i) investigate the readiness of Postgraduates to utilize cloud computing for learning; (ii) examine the influence of gender on readiness of Postgraduates to utilize cloud computing for learning. The study adopted descriptive research design, using quantitative survey method. Six research questions and four hypotheses were answered and tested respectively. A total of three hundred and ninety-eight (398) respondents were randomly sampled. Frequency counts, percentages and mean were employed to answer research questions while hypotheses were tested using t-test and analysis of variance (ANOVA). The findings of the study revealed that: (i) majority of Postgraduates (59.8%) are ready to utilize cloud computing for learning; (ii) no significant difference between male and female undergraduates on their readiness to utilize cloud computing for learning. The study concluded that Postgraduates are ready to utilize cloud computing resources for learning. Thus, the study recommended that Nigerian universities should encourage postgraduates to explore full benefits of cloud computing in other to improve their learning; among many others.Keywords: ICT; Cloud computing; readiness; utilization and learning